Discussion of Corporate Financial Reporting: A Methodological Review of Empirical Research - Gonedes, Nicholas J. (Journal of Accounting Research, 1982)
Nicholas J. Gonedes, Discussion of Corporate Financial Reporting: A Methodological Review of Empirical Research, Journal of Accounting Research, Vol. 20, Supplement: Studies on Current Research Methodologies in Accounting: A Critical Evaluation (1982), pp. 235-238